RESPON BEBERAPA VARIETAS TANAMAN SAWI (Brassica juncea L.) DENGAN PEMBERIAN PUPUK ORGANIK - Philip G. Marpaung; Mbue Kata Bangun; Syafruddin Ilyas (Universitas Sumatera Utara, 2013)
Heritability of some varieties of mustard plants (Brassica juncea L.) with organic fertilizer. Mustardis a vegetable that seasonal and widely cultivated because of their many benefits and rewards.Mustard production has decreased each year. The decreasing availability of land and cultivationmethods are less than the maximum, then powered back organic farming system. The purpose ofthis research was to determine the response of two varieties of mustard with a heritability ofproviding a variety of organic fertilizers. Research conducted in public land Jl.Setia Budi, SelayangSimpang Village, District Field Tuntungan in September to November 2012, using a randomizedblock design with two factors and four replications. The first factor was mustard varieties consistedof Toksakan and Morakot. The second factor was sources of Will Grow organic fertilizer consistedof without Will Grow organic fertilizer, (0.5 x recommended dosage): 31.25 g / plot, (1.00 xrecommended dosage): 62.5 g / plot and (1.50 x recommended dosage): 93.75 g / plot. The resultsshowed that the varieties tested significantly different observation variables plant height, leaf area,leaf chlorophyll amount, selling fresh weight per plant, biomass per sample weight and harvestindex. Fertilizer Will Grow significant effect on the observation variables plant height, leaf area,leaf chlorophyll amount, selling fresh weight per plant, and weight biomass per sample. Highestheritability value contained in the variable observations of the lowest plant height and leaf area atthe observation variables.Keywords : heritability, mustard, variety, fertilizer